2006
DOI: 10.1111/j.1365-2133.2006.07487.x
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic abnormalities in cutaneous squamous cell carcinomas: frequent inactivation of the RB1/p16 and p53 pathways

Abstract: Our findings indicate that the promoter hypermethylation of cancer-related genes, especially CDH1, is frequently shown in SCCs, and dysregulation of the RB1/p16 and/or p53 pathway through either genetic or epigenetic mechanisms, except for epigenetic abnormalities of p53 itself, should contribute to the carcinogenesis of SCCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 31 publications
0
62
1
2
Order By: Relevance
“…It is known that other mechanisms than mutations can cause aberrant expression of p16 and p14, such as loss of parts or the entire short arm of chromosome 9 [33][34][35] or epigenetic events like hypermethylation. 36 However, for p53, a significant association was present between p53 expression and type of mutation, with missense mutations being associated with positive staining, and nonsense and frame shift mutations with negative staining (p ¼ 0.002). Missense mutations can lead to a structurally altered protein that is more stable than the wild type, resulting in higher levels of protein detectable by antibody.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is known that other mechanisms than mutations can cause aberrant expression of p16 and p14, such as loss of parts or the entire short arm of chromosome 9 [33][34][35] or epigenetic events like hypermethylation. 36 However, for p53, a significant association was present between p53 expression and type of mutation, with missense mutations being associated with positive staining, and nonsense and frame shift mutations with negative staining (p ¼ 0.002). Missense mutations can lead to a structurally altered protein that is more stable than the wild type, resulting in higher levels of protein detectable by antibody.…”
Section: Discussionmentioning
confidence: 93%
“…The PM-PCR RHA method has previously been described in detail. 24,26 The method was designed for the identification of 25 established beta-PV types, namely genotypes 5,8,9,12,14,15,17,19,20,21,22,23,24,25,36,37,38,47,49,75,76,80,92,93 and 96.…”
Section: Dna Isolation and Pcr Reactions For Mutation Analysesmentioning
confidence: 99%
“…13 The majority of pancreatic cancer has been found to exist in absence of Smad4 gene, or mutation, and Smad4 inactivation also be found in gastric cancer, colorectal cancer, breast cancer, lung cancer. 14 Our experimental results show that Smad4 in normal gastric mucosa tissues increased even fully expressed which means that the normal cell Smad4 in the regulation role of TGF-β1/Smads signaling pathway is crucial. Yet another study by Rodeck 15 findings on the role of Smad4 is consistent to the findings of the current study.…”
Section: Discussionmentioning
confidence: 69%
“…Similar findings were reported after an analysis of the uterine cervix SCC samples, in which no mutations and few losses of heterozygosity were observed, although PTEN promoter methylation was detected in 58% (23). Murao et al, however, suggested that PTEN methylation was not found in cutaneous SCCs (24). Further study is necessary to determine whether this discrepancy may be based on tissue specificity.…”
Section: Discussionmentioning
confidence: 85%